2019
DOI: 10.1111/anec.12649
|View full text |Cite
|
Sign up to set email alerts
|

Continuous 4‐week ECG monitoring with adhesive electrodes reveals AF in patients with recent embolic stroke of undetermined source

Abstract: BackgroundAtrial fibrillation (AF) frequently escapes routine stroke workup due to its unpredictable and often asymptomatic nature, leaving a significant portion of patients at high risk of recurrent stroke. Recent trials emphasized continuous electrocardiogram (ECG) monitoring in the detection of occult AF. We screened AF in patients meeting the embolic stroke of unknown source (ESUS) criteria using an external miniaturized recorder with an adhesive electrode.MethodsPatients aged ≥50 with recent ESUS were pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…In our previous study, we detected pAF in 12% of the patients in a 4-week monitoring (Lumikari et al, 2019), which was in accordance with prior studies of 1-to 4-week monitoring periods (Sposato et al, 2015). The low pAF detection rate in the present patients (6.7%) was most probably caused by the relatively low age of our patients and limited sample size.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our previous study, we detected pAF in 12% of the patients in a 4-week monitoring (Lumikari et al, 2019), which was in accordance with prior studies of 1-to 4-week monitoring periods (Sposato et al, 2015). The low pAF detection rate in the present patients (6.7%) was most probably caused by the relatively low age of our patients and limited sample size.…”
Section: Discussionsupporting
confidence: 92%
“…The EMBRACE study demonstrated a drastic increase in pAF detection rates using a 30‐day ECG monitor with belt, and multiple studies have afterward provided similar results with either plaster electrodes, wearable ECG, or implantable loop recorders (Gladstone et al., 2014; Israel et al., 2017; Sanna et al., 2014; Wachter et al., 2017). To the best of our knowledge, there are only two studies specifically focusing on ESUS patients with noninvasive monitoring methods, reporting detection rates of 22% in 21‐day monitoring (Rubio Campal et al., 2020) and 12% in 28‐day monitoring (Lumikari et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In patients not eligible for thumb ECG, a device with adhesive electrodes would be an alternative. 35 Although a thumb ECG is an attractive method of non-invasive AF detection, there remain some controversies with regard to anticoagulation for short-term AF. The duration of an AF episode captured by snapshot is unknown, but it is assumed to represent longer or multiple episodes.…”
Section: Limitationsmentioning
confidence: 99%
“…On the other hand, it was proven that long term ECG monitoring during regular daily activities can be very useful in the detection of heart disease in people who had normal 12-lead ECG, and negative Master two-step tests [16]. Furthermore, it was proven that it is possible to detect atrial fibrillation in asymptomatic people with long-term one-channel ECG monitoring [17].…”
Section: Introductionmentioning
confidence: 99%